Employee Engagement Strategy, Organizational Culture and Transformational Leadership Impact on Organizational Commitment - Satria Nugraha; Didin Hikmah Perkasa; Nur Vitriani (Jurnal Manajemen dan Bisnis Madani, 2025)
This study aims to determine the effect of employee engagement, organizational culture and transformational leadership on organizational commitment at the National Amil Zakat Agency (BAZNAS). This type of research uses quantitative methods and implements primary data derived from distributing questionnaires. Having a population of 300 people, sampling in this study used simple random sampling, the selected sample was 100 employees. The analysis technique used in this research is the Partial Least Square (PLS) method and uses the Smart PLS version 3 application. The results showed that Employee Engagement and Transformational Leadership have a positive and significant effect on Organizational Commitment. While Organizational Culture has a positive and insignificant effect on Organizational Commitment.